Identification and analysis of a key long non‐coding RNAs (lncRNAs)‐associated module reveal functional lncRNAs in cardiac hypertrophy. Issue 2 (20th November 2017) - Zhang, Jian; Feng, Chenchen; Song, Chao; Ai, Bo; Bai, Xuefeng; Liu, Yuejuan; Li, Xuecang; Zhao, Jianmei; Shi, Shengshu; Chen, Xin; Su, Xiaojie; Li, Chunquan
Abstract: Cardiac hypertrophy (CH) is a common disease that originates from long‐term heart pressure overload and finally leads to heart failure. Recently, long non‐coding RNAs (lncRNAs) have attracted attention because they have broad and crucial functions in regulating complex biological processes. Some studies had found that lncRNAs play vital roles in complex cardiovascular diseases. However, the function and mechanism of lncRNAs in CH have not been elucidated. In our study, to investigate the potential roles of lncRNAs in CH, the Cardiac Hypertrophy‐associated LncRNAs‐Protein coding genes Network (CHLPN) was constructed by integrating gene microarray re‐annotation and subpathway enrichment analyses. After performing random walking with restart in CHLPN, we predicted 21 significant risk lncRNAs, of which 7 (Kis2, 1700110K17Rik, Gm17501, E330017L17Rik, C630043F03Rik, Gm9866 and Ube4bos1) formed a close module with their co‐expressed protein‐coding genes (PCGs). We found that the module might play crucial roles in the development of CH. In particular, 44 PCGs that were co‐expressed with six lncRNAs were enriched in CH‐related biological processes and pathways. We also found that some lncRNAs participated in the competitive endogenous RNA cross‐talk that might be involved in CH. These results indicate that the functional lncRNAs are related to post‐transcriptional regulation and could shed light on a new molecular diagnostic target of CH.